Islamic Studies in a Secular Republic: New Directions in Higher Education Transformation in Azerbaijan - Aliyev, Tural Kamal; Hasanova, Narmin Rashad qizi (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2026)
This article examines the changing trajectory of Islamic higher education in Azerbaijan, with particular attention to how Islamic Studies is being reconfigured within a constitutionally secular republic. It argues that the transformation of Islamic higher education in the country cannot be understood simply as the revival of religious learning after the Soviet period, but rather as the emergence of a new academic model shaped by state policy, institutional reform, and the need to reconcile religious scholarship with modern higher education standards. Using a qualitative library-based approach, the article analyzes policy documents, institutional materials, and scholarly discussions related to the development of Islamic higher education in contemporary Azerbaijan. The study focuses especially on the role of the Azerbaijan Institute of Theology as a key site for the institutionalization of Islamic Studies within a state-regulated educational framework. The findings suggest that Islamic higher education in Azerbaijan is undergoing a dual transformation: first, from informal or traditionally bounded religious learning toward formalized university-based education; and second, from narrowly confessional instruction toward a broader interdisciplinary structure that incorporates theology, religious studies, and selected social-scientific perspectives. This transformation reflects a distinctive national model in which secular governance does not eliminate Islamic higher education, but instead reshapes its institutional boundaries, epistemic orientation, and public function. The article contributes to broader debates on Islamic higher education by showing how religious knowledge is reconstructed in post-Soviet Muslim societies under secular state frameworks.